Geochemistry of the Main Rock Forming Minerals in The Perhentian Kecil Syenite, Besut, Terengganu - A Ghani, Azman (Malaysian Journal of Science, 2003)
The Perhentian Kecil Syenite consists of variety of igneous rocks ranging in composition from syenitic to monzonitic and even gabbroic rocks. The essential minerals in Perhentian Kecil Syenite are K-feldspar, plagioclase, hornblende, pyroxene, quartz, biotite, sphene, epidote, apatite, zircon and magnetite. Composition of K-feldspar in Perhentian Kecil Syenite is near to pure orthoclase with An percentage less than 1%. Plagioclase composition range from oligoclase to andesine. Magnesiohornblende is the main amphibole type and the crystals show an increase of $Ti0_{2}$ and $Al^{iv}$ and decrease in $CaO$ from core to rim. The deduced magmatic crystallisation interval for the hornblende is in the range of 660 to 780 °C (± 70°C). Composition of the sphene plot in igneous sphene field and is similar to those from the Victoria Range granitic rocks, South Island, New Zealand. Apatite can be divided into clear and clouded parts and the latter contain higher $Si0_{2}$, $K_{2}0$, $Fe(tot)$ and $BaO$. Both $CaO$ and $P_{2}O$ have a wider range in the clouded part compared to the clear part of apatite. Magnetite is the most common opaque mineral in the Perhentian Kecil Syenite.